FORCED MARRIAGE OF VICTIMS OF SEXUAL VIOLENCE AS A FORM OF SETTLEMENT IN VICTIMOLOGICAL PERSPECTIVE - Shinta Diva; Gialdah Tapiansari Batubara (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
Ratification of RUU TPKS has become a strong legal for victims of sexual violence crimes, one of its scopes listed in Article 4 of the UU TPKS on forced marriage. Referring to the Academic Text of the RUU PKS, forced marriage means if any person who abuses power or threats of violences or deceits or persuasion or a series of lies or other psychic pressures so that a person cannot give a real consent to perform a marriage. Through the perspective of victimology, it can be seen the impact of a crime on victims and the protection of victims in the criminal justice system. This research method uses a normative juridical approach which is a research approach by studying, viewing, and examining several theoretical matters concerning legal principles, conceptions, views, theories, legal regulations and the legal system relating to the issues being discussed. This research aims to find out prevent the handling of victims of sexual violence crimes with inappropriate or deviant forms of settlement. One of them is the forced marriage.